2010
DOI: 10.5194/acp-10-4673-2010
|View full text |Cite
|
Sign up to set email alerts
|

How can aerosols affect the Asian summer monsoon? Assessment during three consecutive pre-monsoon seasons from CALIPSO satellite data

Abstract: Abstract. The impact of aerosols above and around the Tibetan Plateau on the Asian Summer Monsoon during pre-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
2
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(87 citation statements)
references
References 34 publications
3
81
2
1
Order By: Relevance
“…The land-ocean contrast in radiative forcing observed at the TOA is not seen within the atmosphere, because the spatial distribution of dust-induced atmospheric heating is mainly determined by dust concentration rather than surface properties. However, some studies have proposed that dust aerosols can absorb SW radiation more effectively over bright surfaces than over dark surfaces due to multiple reflections of SW radiation between overlying dust layers and bright land surfaces (Lau et al, 2006;Kuhlmann and Quaas, 2010). At the surface, dust aerosols block SW radiation from reaching the surface through scattering and absorption, which results in a surface cooling effect as shown in Fig.…”
Section: Radiative Effect Of Dustmentioning
confidence: 99%
See 3 more Smart Citations
“…The land-ocean contrast in radiative forcing observed at the TOA is not seen within the atmosphere, because the spatial distribution of dust-induced atmospheric heating is mainly determined by dust concentration rather than surface properties. However, some studies have proposed that dust aerosols can absorb SW radiation more effectively over bright surfaces than over dark surfaces due to multiple reflections of SW radiation between overlying dust layers and bright land surfaces (Lau et al, 2006;Kuhlmann and Quaas, 2010). At the surface, dust aerosols block SW radiation from reaching the surface through scattering and absorption, which results in a surface cooling effect as shown in Fig.…”
Section: Radiative Effect Of Dustmentioning
confidence: 99%
“…The Indian summer monsoon (ISM) region and its surrounding areas have been identified as having high aerosol concentrations (e.g., Kuhlmann and Quaas, 2010) and this large aerosol loading has been increasing dramatically during the past decade due to population growth and more frequent dust activity (Hsu et al, 2012). The potential impacts of aerosols on ISM is an important issue because about one-third of the world's population rely heavily on the ISM rainfall for water supply and agricultural production.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Misra et al (2012) have also reported higher extinction values at altitudes of 2-4 km during dust loading period of April-June over Kanpur using MPLNET and CALIPSO datasets. In another study, Kuhlmann and Quaas (2010) PDR and CR values can be effectively used in differentiation between spherical and non-spherical as well as smaller and larger particles (Liu et al, 2008). A higher value of CR (~1.0) and PDR (~0.2) indicates the dominance of larger dust particles in the atmosphere, whereas relatively lower values suggest the presence of BB or U-I pollution particles (Mishra and Shibata, 2012a).…”
Section: Aerosol Properties From Space-and Ground-based Remote Sensorsmentioning
confidence: 99%